Does an increase in number of deep burrowing earthworms enhance subsurface nutrient losses? - Nuutinen, Visa; Kaseva, Janne; Lemola, Riitta; Tähtikarhu, Mika; Butt, Kevin R.; Lill, Jan-Olof; Slotte, Joakim M.K.; Uusitalo, Risto (Wiley-Blackwell, 2026)
Deep burrowing earthworms Lumbricus terrestris can be abundant along subdrain trenches, creating macropores that may serve as preferential flow paths for particles and agrochemicals to subdrains. We examined L. terrestris abundance, subdrain water discharge, and nutrient loss trends during 2002–2022 in an arable no-till clay soil with an emerging L. terrestris density gradient. Additionally, we analyzed subdrain water discharge during heavy rainfall events and traced material movement from topsoil to subsurface drains utilizing a 137Cs marker. Between 2003 and 2009, inoculated L. terrestris started to establish at the upper edge of the field site and successive samplings revealed gradual population growth and colonization downslope. Along the 134 m field strips (N = 2), a L. terrestris mean burrow count in 2022 reached 37 m−2 (range 29–54) with a mean individual count of 27 m−2 (13–54) at the upper edge close to the inoculation area, but on average only 5 burrows (0–8) and 2 individuals m−2 (0–8) were recorded at the lower edge. Simultaneously with L. terrestris spreading, water, sediment and nutrient discharges via subsurface drains nearly doubled. Despite these concomitant trends, statistical analyses did not support the hypothesis that long-term drainage discharges were coupled with the L. terrestris gradient. Neither were storm water discharges, nor topsoil (specifically 137Cs) migration to drains in agreement with the L. terrestris gradient. Long-term increase in discharges were likely due to increased precipitation outside the growing season (2002–2022 trend for Oct-Apr precip. +2.4 mm year−1) and increasing winter/spring temperatures (2002–2022 trend for Jan-Mar temp. +0.12 deg. year−1). Additionally, different backfill materials of the upper (topsoil) and lower (wood chips) parts of the field may have affected the results. Under the given environmental conditions and cultivation, the agronomic benefits of L. terrestris activity do not appear to come with a cost of increased subdrain leaching.
Keywords: bioturbation; boreal climate; earthworm inoculation; Lumbricus terrestris; macropores; nitrogen; no-till; phosphorus; preferential flow; subdrainage